Heinrich Heine in Paris: the poetics and politics of self-fashioning - Elder, L (2011)
Drawing on the concept developed in Stephen Greenblatt’s Renaissance Self-fashioning: From More to Shakespeare, this thesis presents Heinrich Heine as an extreme case of the ‘self-fashioning’ writer. I argue that his preoccupation with self-construction determines what and how he writes, how he treats his reading public and, crucially, how he perceives and evaluates his own career. Though self-fashioning occurs in his earliest works, Heine’s decision to move to Paris (1831) was the single biggest self-determining act of his life; he constructs it as a moment of rebirth. Inspired by the July Revolution, he sought a new authorial identity in harmony with the supposed new world order and his own social, political and artistic ideals. However, the reality of juste-milieu society—a continual seesawing between modernisation and restoration—cast doubt on the possibility, even the desirability, of novelty and progress, the goals of revolution. In this context, Heine cultivates the identity of a perpetually embattled writer through confrontational dialogue with contemporary ideologies and his readership alike; ever ambivalent in his attitude to the role of art in a modernising world, he is also engaged in an internal battle with the self. First I show how he establishes himself in the role of cultural correspondent in the early journalism by developing a mode of self-conscious spectatorship which enables him to negotiate between contemporary French conditions and German readership expectations. Second I investigate the strategies he uses to free himself from his Buch der Lieder legacy and redefine his identity as a poet in Paris; I show how the Neue Gedichte (1844) are assembled to record and reflect on this transitional process, making the collection a monument to his self-fashioning tendencies. Finally I explore how Heine manipulates the relationship between public and private within a concept of self to construct his authorial identity; I consider a number of self-editing and self-reconstructive practices in prefaces, letters and autobiographical writing.